Polarizing plate with phase difference layer

By using polycarbonate-based resin and a polarizing plate with a phase difference layer with a specific stretching treatment, the whitening and cracking problems in the prior art are solved, and excellent dimensional stability and display effects are achieved, and suitable for image display devices.

CN113631972BActive Publication Date: 2025-01-03NITTO DENKO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080024427.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-27
Filing Date
2020-03-18
Publication Date
2025-01-03
Estimated Expiration
2040-03-18

AI Technical Summary

Technical Problem

The existing polarizer with phase difference layer is prone to whitening and cracks during use, and the dimensional stability is insufficient, which affects the display effect of the observation image display device.

Method used

Polycarbonate resin is used as the phase difference layer material, combined with specific stretching treatment and structural design, to form a polarizing plate with phase difference layer with excellent optical and mechanical characteristics, including polarizers, protective layers, and phase difference layers. Re(450)/Re(550) is 0.98-1.03, Re(550) is 80nm-190nm, and the moisture permeability is 100g/m2·24h or less, and dimensional stability is maintained in a high temperature and high humidity environment.

Benefits of technology

It effectively suppresses the occurrence of whitening and cracks, improves dimensional stability, ensures the display effect of the image display device, and is suitable for the viewing side of the image display device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113631972B_ABST
    Figure CN113631972B_ABST
Patent Text Reader

Abstract

A polarizing plate with a phase difference layer is provided, which has suppressed whitening and cracking and excellent dimensional stability. The polarizing plate with a phase difference layer of the present application has a phase difference layer and a polarizing plate in sequence, wherein the polarizing plate has a polarizer and a protective layer, and the phase difference layer contains a polycarbonate resin, Re(450) / Re(550) is 0.98 to 1.03, and Re(550) is 80 nm to 190 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polarizing plate with a phase difference layer. Background Art

[0002] In order to improve the viewing performance when observing the display screen of an image display device while wearing polarized sunglasses, an image display device comprising a polarizing plate with a phase difference layer is known, wherein the polarizing plate with a phase difference layer uses a λ / 4 plate as a protective substrate of the polarizing plate on the viewing side (Patent Document 1). However, when the polarizing plate with a phase difference layer as described above is used on the viewing side of the image display device, whitening and / or cracks may occur with use, and further, the dimensional stability may be insufficient.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 10-10523 Summary of the invention

[0006] Problem that the invention aims to solve

[0007] The present invention has been made to solve the above-mentioned conventional problems, and an object of the present invention is to provide a polarizing plate with a retardation layer which is suppressed in whitening and cracking and has excellent dimensional stability.

[0008] Solutions for solving problems

[0009] The polarizing plate with a phase difference layer in an embodiment of the present invention is arranged on the viewing side of the image display device, and the polarizing plate with a phase difference layer has a phase difference layer and a polarizing plate in sequence from the viewing side, and the polarizing plate has a polarizer and a protective layer. The phase difference layer contains a polycarbonate resin, Re(450) / Re(550) is 0.98~1.03, and Re(550) is 80nm~190nm.

[0010] In one embodiment, the polycarbonate-based resin includes a structural unit derived from a dihydroxy compound represented by the following formula (4).

[0011]

[0012] In one embodiment, the polycarbonate-based resin further includes a structural unit derived from an alicyclic dihydroxy compound, and the alicyclic dihydroxy compound is represented by the following general formula (II): 1 It is the structure shown in the following (IIb), where n=0.

[0013] HOCH2-R 1 -CH2OH (II)

[0014]

[0015] In one embodiment, the polarizing plate with a retardation layer is suppressed from cracking in an irregular shape processability test.

[0016] In one embodiment, the polarizing plate with a retardation layer is suppressed from whitening and cracking in a sebum resistance test.

[0017] In one embodiment, the polarizing plate with a retardation layer has its dimensional change suppressed in a dimensional stability test.

[0018] In one embodiment, the moisture permeability of the phase difference layer is 100 g / m 2 Less than 24 hours.

[0019] In one embodiment, the phase difference change of the phase difference layer after being stored for 500 hours under the conditions of a temperature of 65° C. and a humidity of 90% is 1.5% or less.

[0020] In one embodiment, the polarizing plate with a retardation layer is in a long strip shape, and the retardation layer is an obliquely stretched film having a slow axis in a direction forming an angle of 40° to 50° with respect to the longitudinal direction.

[0021] Effects of the Invention

[0022] According to an embodiment of the present invention, in a polarizing plate with a phase difference layer which is arranged on the viewing side of an image display device and has a phase difference layer and a polarizing plate in sequence from the viewing side, the polarizing plate has a polarizer and a protective layer. By making the phase difference layer contain a polycarbonate resin, and making Re(450) / Re(550) 0.98 to 1.03, and Re(550) 80nm to 190nm, it is possible to realize a polarizing plate with a phase difference layer in which whitening and cracking are suppressed and dimensional stability is excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic cross-sectional view of a polarizing plate with a retardation layer according to one embodiment of the present invention. DETAILED DESCRIPTION

[0024] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0025] (Definition of terms and symbols)

[0026] The definitions of terms and symbols in this specification are as follows.

[0027] (1) Refractive index (nx, ny, nz)

[0028] "nx" is the refractive index in the direction where the in-plane refractive index reaches the maximum (ie, the slow axis direction), "ny" is the refractive index in the in-plane direction orthogonal to the slow axis (ie, the fast axis direction), and "nz" is the refractive index in the thickness direction.

[0029] (2) In-plane phase difference (Re)

[0030] "Re(λ)" is the in-plane phase difference measured at 23°C using light of wavelength λnm. For example, "Re(550)" is the in-plane phase difference measured at 23°C using light of wavelength 550nm. When the thickness of the layer (film) is d(nm), Re(λ) is calculated by the formula Re(λ) = (nx-ny)×d.

[0031] (3) Retardation in the thickness direction (Rth)

[0032] "Rth(λ)" is the phase difference in the thickness direction measured using light of wavelength λnm at 23°C. For example, "Rth(550)" is the phase difference in the thickness direction measured using light of wavelength 550nm at 23°C. When the thickness of the layer (film) is d(nm), Rth(λ) is calculated by the formula Rth(λ) = (nx-nz) × d.

[0033] (4) Nz coefficient

[0034] The Nz coefficient is obtained by Nz=Rth / Re.

[0035] (5) Angle

[0036] When an angle is mentioned in this specification, the angle includes both clockwise and counterclockwise angles relative to a reference direction. Therefore, for example, "45°" means ±45°.

[0037] A. Overall structure of polarizing plate with phase difference layer

[0038] Figure 1 It is a schematic cross-sectional view of a polarizing plate with a phase difference layer according to one embodiment of the present invention. The polarizing plate with a phase difference layer is used on the viewing side of an image display device. The polarizing plate 100 with a phase difference layer of the present embodiment has a phase difference layer 20 and a polarizing plate 10 in order from the viewing side. The polarizing plate 10 includes: a polarizer 11, a first protective layer 12 arranged on one side of the polarizer 11, and a second protective layer 13 arranged on the other side of the polarizer 11. Depending on the purpose, one of the first protective layer 12 and the second protective layer 13 can be omitted. The angle formed by the absorption axis of the polarizer 11 and the slow axis of the phase difference layer 20 is, for example, 40° to 50°, preferably 42° to 48°, and more preferably 44° to 46°. The polarizing plate with a phase difference layer may have a hard coating layer (not shown) on the viewing side of the phase difference layer 20 as needed.

[0039] In the polarizing plate 100 with a phase difference layer, a conductive layer or an isotropic substrate with a conductive layer (not shown) may be provided. Typically, the conductive layer or the isotropic substrate with a conductive layer is provided on the outer side of the polarizing plate 10 (the side opposite to the phase difference layer 20). When a conductive layer or an isotropic substrate with a conductive layer is provided, the polarizing plate with a phase difference layer can be applied to a so-called internal touch panel type input display device in which a touch sensor is assembled between an image display unit and a polarizing plate. In this case, the effect of the present invention is significant.

[0040] In an embodiment of the present invention, the retardation layer includes a polycarbonate resin, Re(450) / Re(550) is 0.98 to 1.03, and Re(550) is 80 nm to 190 nm.

[0041] The polarizing plate with a phase difference layer of the present invention can be in the form of a single sheet or in the form of an elongated strip. In this specification, "elongated strip" refers to an elongated shape that is sufficiently long relative to the width, for example, including an elongated shape whose length is more than 10 times, preferably more than 20 times relative to the width. The elongated polarizing plate with a phase difference layer can be wound into a roll. When the polarizing plate with a phase difference layer is in the form of an elongated strip, the polarizing plate and the phase difference layer are also in the form of elongated strips. At this time, the polarizer preferably has an absorption axis along the length direction. The phase difference layer is preferably an obliquely stretched film having a slow axis in a direction at an angle of, for example, 40° to 50° relative to the length direction. If the polarizer and the phase difference layer are of this structure, the polarizing plate with a phase difference layer can be produced by roll-to-roll.

[0042] In practical terms, an adhesive layer (not shown) is provided on the side of the polarizing plate opposite to the phase difference layer, and the polarizing plate with the phase difference layer can be attached to the image display unit. Furthermore, it is preferred that a release film is temporarily adhered to the side of the adhesive layer opposite to the polarizing plate until the polarizing plate with the phase difference layer is used. By temporarily adhering the release film, a roll can be formed while protecting the adhesive layer.

[0043] The polarizing plate with a phase difference layer has cracks suppressed in the irregular shape processability test. That is, the polarizing plate with a phase difference layer can also be used well in applications requiring irregular shapes. This advantage can be obtained by making the phase difference layer of the polarizing plate with a phase difference layer include a specific polycarbonate resin described later.

[0044] The polarizing plate with a phase difference layer is inhibited from whitening and cracking in the sebum resistance test. That is, the polarizing plate with a phase difference layer can maintain good properties even if it contacts the user's skin (such as fingertips) multiple times due to long-term use. Therefore, the polarizing plate with a phase difference layer can be suitably used in an internal touch panel input display device. The phase difference layer included in the polarizing plate with a phase difference layer can obtain this advantage by including a specific polycarbonate resin described later.

[0045] The thermal shrinkage of the polarizing plate with a phase difference layer in the dimensional stability test is suppressed. That is, the polarizing plate with a phase difference layer can maintain good properties even in a high temperature and high humidity environment. This advantage can be obtained by forming a phase difference layer by stretching a specific resin film containing a polycarbonate resin described later using a specific stretching method and stretching conditions described later.

[0046] Hereinafter, the components of the polarizing plate with a retardation layer will be described in more detail.

[0047] B.Polarizing plate

[0048] B-1. Polarizer

[0049] Any appropriate polarizer may be adopted as the polarizer. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.

[0050] Specific examples of polarizers composed of a single-layer resin film include: polarizers obtained by dyeing and stretching hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films using dichroic substances such as iodine and dichroic dyes; polyene-based oriented films such as dehydrated PVA and dehydrochlorinated polyvinyl chloride films, etc. From the perspective of excellent optical properties, it is preferred to use a polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it.

[0051] The above-mentioned iodine-based dyeing is carried out by, for example, immersing the PVA film in an iodine aqueous solution. The stretching ratio of the above-mentioned uniaxial stretching is preferably 3 to 7 times. The stretching can be carried out after the dyeing treatment, or it can be carried out while dyeing. In addition, it is also possible to dye after stretching. As needed, the PVA film is subjected to swelling treatment, cross-linking treatment, cleaning treatment, drying treatment, etc. For example, by immersing the PVA film in water before dyeing and washing it with water, it is not only possible to wash away the dirt and anti-blocking agent on the surface of the PVA film, but also possible to swell the PVA film to prevent uneven dyeing.

[0052] As a specific example of a polarizer obtained using a laminate, there can be cited: a laminate using a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. The details of the manufacturing method of such a polarizer are recorded in, for example, Japanese Patent Publication No. 2012-73580 and Japanese Patent No. 6470455. The records of these patent documents can be cited in this specification as a reference. The entire record of the gazette is cited in this specification as a reference.

[0053] In one embodiment, the thickness of the polarizer is preferably 1 μm to 25 μm, more preferably 3 μm to 10 μm, and further preferably 3 μm to 8 μm. If the thickness of the polarizer is within this range, warping during heating can be well suppressed and good appearance durability during heating can be obtained.

[0054] B-2. Protective layer

[0055] The protective layer is formed by any and appropriate protective film that can be used as a film to protect the polarizer. As a specific example of the material that becomes the main component of the protective film, cellulose resins such as triacetyl cellulose (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyethersulfone resins, polysulfone resins, polystyrene resins, polynorbornene resins, polyolefin resins, (meth) acrylic resins, acetate resins, etc. can be listed. In addition, thermosetting resins or ultraviolet curing resins such as (meth) acrylic resins, carbamate resins, (meth) acrylic acid carbamate resins, epoxy resins, and silicone resins can also be listed. In addition, glassy polymers such as siloxane polymers can also be listed. In addition, polymer films recorded in Japanese Patent Publication No. 2001-343529 (WO01 / 37007) can also be used. As the material of the film, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain can be used, and for example, a resin composition containing an alternating copolymer formed of isobutylene and N-methylmaleimide and an acrylonitrile-styrene copolymer can be cited. The polymer film can be, for example, an extrusion molding of the above resin composition.

[0056] When the second protective layer 13 is provided, the inner protective layer is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane phase difference Re (550) is 0nm to 10nm, and the phase difference Rth (550) in the thickness direction is -10nm to +10nm. The protective layer can be made of any and appropriate material as long as the optical body is isotropic. The material can be appropriately selected from the materials described above for the protective layer.

[0057] The thickness of the protective film is preferably 10 μm to 100 μm. The protective layer may be laminated on the polarizer via an adhesive layer (specifically, an adhesive layer or a pressure-sensitive adhesive layer), or may be laminated on the polarizer in close contact (without an adhesive layer).

[0058] C. Phase difference layer

[0059] The retardation layer of the embodiment of the present invention is formed of a retardation film. The retardation film of the embodiment of the present invention contains a polycarbonate resin. Typically, the retardation film of the embodiment of the present invention is a stretched film of a polycarbonate resin film.

[0060] The above-mentioned phase difference film shows a flat wavelength dispersion characteristic in which the phase difference value hardly changes with the wavelength of the measured light. The Re(450) / Re(550) of the phase difference film is 0.98-1.03, preferably 0.99-1.03, and more preferably 1.00-1.03. By using a polycarbonate resin that can obtain such Re(450) / Re(550) to form a phase difference film, it is possible to obtain a polarizing plate with a phase difference layer in which whitening and cracking in a sebum resistance test are suppressed and irregular shape processability and dimensional stability are excellent. Furthermore, if it is such a wavelength dispersion characteristic, excellent anti-reflection characteristics can be achieved in a wide band.

[0061] The refractive index characteristics of the above-mentioned retardation film preferably show the relationship of nz>nx=ny or nx>ny≥nz. The in-plane retardation Re(550) of the above-mentioned retardation layer film is 80nm~190nm, preferably 100nm~170nm, and more preferably 120nm~150nm. That is, the retardation film can function as a λ / 4 plate.

[0062] The Nz coefficient of the retardation film is preferably 0.9 to 1.5, and more preferably 0.9 to 1.3. When the Nz coefficient is within such a range, an image display device having excellent viewing angle dependence of reflectance and reflection hue can be obtained.

[0063] The moisture permeability of the retardation film is preferably 100 g / m 2 · 24h or less, more preferably 90g / m 2 ·24h or less. The lower limit can be, for example, 1g / m 2 · 24h. When the moisture permeability of the retardation film is within such a range, there is an advantage that a change in retardation in a humidified environment can be suppressed.

[0064] The phase difference change of the above-mentioned phase difference film after being stored for 500 hours under the conditions of temperature 65°C and humidity 90% (humidification test) is preferably 1.5% or less, more preferably 1.0% or less. The lower limit can be, for example, 0.01%. The above-mentioned phase difference change (%) is expressed by |(Re 500 = -Re0) / Re0|×100(%). Re0 is the in-plane retardation of the retardation film before the test (nm), Re 500 If the phase difference of the phase difference film is within this range, the following advantages can be obtained: the hue change caused by the phase difference at each position on the image display device is reduced, and the occurrence of color unevenness in the display is suppressed.

[0065] The thickness of the retardation film can be appropriately set so that it can function as a λ / 4 plate, and the thickness is preferably 20 μm to 60 μm, more preferably 20 μm to 50 μm, and further preferably 25 μm to 40 μm.

[0066] The absolute value of the photoelastic coefficient of the retardation film is preferably 2×10 -11 m 2 / N or less, more preferably 2.0×10 -13 m 2 / N~1.5×10 -11 m 2 / N, more preferably 1.0×10 -12 m 2 / N~1.2×10 -11 m 2 When the absolute value of the photoelastic coefficient is within this range, the phase difference is unlikely to change when shrinkage stress is generated during heating. As a result, thermal unevenness in the resulting image display device can be well prevented.

[0067] (Resin film)

[0068] As described above, the phase difference film is typically a stretched film of a polycarbonate resin film.

[0069] (Polycarbonate resin)

[0070] The polycarbonate resin of the present invention contains at least a structural unit derived from a dihydroxy compound having a bonding structure represented by the following structural formula (1), and is produced by reacting a dihydroxy compound containing at least a dihydroxy compound having at least one bonding structure -CH2-O- in the molecule with a carbonate diester in the presence of a polymerization catalyst.

[0071]

[0072] Here, as the dihydroxy compound having a bonding structure shown in the structural formula (1), any compound of any structure can be used as long as it has two alcoholic hydroxyl groups, contains a structure having a connecting group -CH2-O- in the molecule, and can react with a carbonic acid diester in the presence of a polymerization catalyst to form a polycarbonate, and multiple compounds can be used in combination. In addition, as the dihydroxy compound used in the polycarbonate resin of the present invention, a dihydroxy compound that does not have a bonding structure shown in the structural formula (1) can also be used in combination. In the following, the dihydroxy compound having a bonding structure shown in the structural formula (1) is sometimes abbreviated as a dihydroxy compound (A), and the dihydroxy compound that does not have a bonding structure shown in the structural formula (1) is sometimes abbreviated as a dihydroxy compound (B).

[0073] (Dihydroxy compound (A))

[0074] The "linking group -CH2-O-" in the dihydroxy compound (A) refers to a structure in which atoms other than hydrogen atoms are bonded to each other to form a molecule. In the linking group, the atom that can at least bond to an oxygen atom or the atom that can bond to both a carbon atom and an oxygen atom is most preferably a carbon atom. The number of "linking groups -CH2-O-" in the dihydroxy compound (A) is preferably 1 or more, more preferably 2 to 4.

[0075] More specifically, examples of the dihydroxy compound (A) include 9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-methylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-isopropylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-isobutylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-tert-butylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-cyclohexylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-phenylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3,5-dimethylphenyl)fluorene, 9 Compounds having an aromatic group in the side chain and an ether group bonded to the aromatic group in the main chain as exemplified by 9-bis(4-(2-hydroxyethoxy)-3-tert-butyl-6-methylphenyl)fluorene and 9,9-bis(4-(3-hydroxy-2,2-dimethylpropoxy)phenyl)fluorene; bis[4-(2-hydroxyethoxy)phenyl]methane, bis[4-(2-hydroxyethoxy)phenyl]diphenylmethane, 1,1-bis[4-(2-hydroxyethoxy)phenyl]ethane, 1,1-bis[4-(2-hydroxyethoxy)phenyl]-1-phenylethane, 2,2-bis[4-(2-hydroxyethoxy)phenyl]propane, 2,2-bis[4-(2-hydroxyethoxy)-3-methylphenyl]propane, 2,2- Bis[3,5-dimethyl-4-(2-hydroxyethoxy)phenyl]propane, 1,1-bis[4-(2-hydroxyethoxy)phenyl]-3,3,5-trimethylcyclohexane, 1,1-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane, 1,4-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane, 1,3-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane, 2,2-bis[4-(2-hydroxyethoxy)-3-phenylphenyl]propane, 2,2-bis[(2-hydroxyethoxy)-3-isopropylphenyl]propane, 2,2-bis[3-tert-butyl-4-(2-hydroxyethoxy)phenyl]propane, 2,2-bis[4-(2-hydroxyethoxy)phenyl]butane, 2,2 - bis(hydroxyalkoxyaryl)alkanes such as bis[4-(2-hydroxyethoxy)phenyl]-4-methylpentane, 2,2-bis[4-(2-hydroxyethoxy)phenyl]octane, 1,1-bis[4-(2-hydroxyethoxy)phenyl]decane, 2,2-bis[3-bromo-4-(2-hydroxyethoxy)phenyl]propane, and 2,2-bis[3-cyclohexyl-4-(2-hydroxyethoxy)phenyl]propane; bis(hydroxyalkoxyaryl)cycloalkanes such as 1,1-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane, 1,1-bis[3-cyclohexyl-4-(2-hydroxyethoxy)phenyl]cyclohexane, and 1,1-bis[4-(2-hydroxyethoxy)phenyl]cyclopentane;Dihydroxyalkoxydiaryl ethers such as 4,4'-bis(2-hydroxyethoxy)diphenyl ether and 4,4'-bis(2-hydroxyethoxy)-3,3'-dimethyldiphenyl ether; bishydroxyalkoxyaryl sulfides such as 4,4'-bis(2-hydroxyethoxyphenyl) sulfide and 4,4'-bis[4-(2-dihydroxyethoxy)-3-methylphenyl] sulfide; bishydroxyalkoxyaryl sulfoxides such as 4,4'-bis(2-hydroxyethoxyphenyl) sulfoxide and 4,4'-bis[4-(2-dihydroxyethoxy)-3-methylphenyl] sulfoxide; 4,4'-bis(2-hydroxyethoxyphenyl) sulfone, 4,4'-bis[4-(2-dihydroxyethoxy)-3-methylphenyl] sulfoxide; bishydroxyalkoxyaryl sulfones such as those exemplified by 1,4-bishydroxyethoxybenzene, 1,3-bishydroxyethoxybenzene, 1,2-bishydroxyethoxybenzene, 1,3-bis[2-[4-(2-hydroxyethoxy)phenyl]propyl]benzene, 1,4-bis[2-[4-(2-hydroxyethoxy)phenyl]propyl]benzene, 4,4'-bis(2-hydroxyethoxy)biphenyl, 1,3-bis[4-(2-hydroxyethoxy)phenyl]-5,7-dimethyladamantane, anhydrous sugar alcohols represented by dihydroxy compounds represented by the following formula (4); and compounds having a cyclic ether structure such as spiroglycol represented by the following general formula (6), which may be used alone or in combination of two or more. ;

[0076]

[0077] These dihydroxy compounds (A) can be used alone or in combination of two or more. In the present invention, as the dihydroxy compound represented by the aforementioned formula (4), isosorbide, isomannide, and isoidide, which are in a stereoisomer relationship, can be listed, and they can be used alone or in combination of two or more.

[0078] It should be noted that among the dihydroxy compounds (A), isosorbide obtained by dehydration condensation of sorbitol produced from various starches that are abundant and easily available as resources is the most preferred from the aspects of ease of acquisition and manufacture, optical properties, and formability. In the present invention, isosorbide is suitably used as the dihydroxy compound (A).

[0079] (Dihydroxy compound (B))

[0080] In the present invention, as the dihydroxy compound, a dihydroxy compound (B) can be used, which is a dihydroxy compound other than the dihydroxy compound (A). As the dihydroxy compound (B), for example, alicyclic dihydroxy compounds, aliphatic dihydroxy compounds, oxyalkylene glycols, aromatic dihydroxy compounds, diols having a cyclic ether structure can be used as dihydroxy compounds forming structural units of polycarbonate, and can be used together with the dihydroxy compound (A), for example, a dihydroxy compound represented by formula (4).

[0081] The alicyclic dihydroxy compound that can be used in the present invention is not particularly limited, and preferably a compound that generally contains a five-membered ring structure or a six-membered ring structure is used. In addition, the six-membered ring structure can be fixed into a chair shape or a boat shape by means of a covalent bond. By making the alicyclic dihydroxy compound a five-membered ring or a six-membered ring structure, the heat resistance of the obtained polycarbonate can be improved. The number of carbon atoms contained in the alicyclic dihydroxy compound is generally 70 or less, preferably 50 or less, and more preferably 30 or less. The larger the value, the higher the heat resistance, but it is difficult to synthesize or difficult to purify or the cost is expensive. The smaller the number of carbon atoms, the easier it is to purify and the easier it is to obtain.

[0082] Specific examples of the alicyclic dihydroxy compound containing a five-membered ring structure or a six-membered ring structure that can be used in the present invention include alicyclic dihydroxy compounds represented by the following general formula (II) or (III).

[0083] HOCH2-R 1 -CH2OH (II)

[0084] HO-R 2 -OH (III)

[0085] (In formula (II) and (III), R 1 , R 2 They represent cycloalkylene groups having 4 to 20 carbon atoms.

[0086] Regarding cyclohexanedimethanol as the alicyclic dihydroxy compound represented by the general formula (II), R 1 The following general formula (IIa) (wherein, R 3 represents an alkyl group having 1 to 12 carbon atoms or a hydrogen atom). Specific examples of such isomers include 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol.

[0087]

[0088] Regarding tricyclodecane dimethanol and pentacyclopentadecanedimethanol as the alicyclic dihydroxy compound represented by the general formula (II), R1 Various isomers are represented by the following general formula (IIb) (wherein n represents 0 or 1).

[0089]

[0090] Regarding decahydronaphthalene dimethanol or tricyclotetradecane dimethanol as the alicyclic dihydroxy compound represented by the general formula (II), R 1 Various isomers represented by the following general formula (IIc) (wherein m represents 0 or 1). Specific examples of such isomers include 2,6-decalinedimethanol, 1,5-decalinedimethanol, and 2,3-decalinedimethanol.

[0091]

[0092] In addition, regarding the norbornane dimethanol as the alicyclic dihydroxy compound represented by the general formula (II), R 1 Various isomers are represented by the following general formula (IId). Specific examples of such isomers include 2,3-norbornane dimethanol and 2,5-norbornane dimethanol.

[0093]

[0094] The alicyclic dihydroxy compound represented by the general formula (II) is adamantane dimethanol, which includes R 1 Various isomers are represented by the following general formula (IIe). Specific examples of such isomers include 1,3-adamantanedimethanol and the like.

[0095]

[0096] In addition, cyclohexanediol as the alicyclic dihydroxy compound represented by the general formula (III) includes R 2 The following general formula (IIIa) (wherein, R 3 represents an alkyl group having 1 to 12 carbon atoms or a hydrogen atom). Specific examples of such isomers include 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1,4-cyclohexanediol, and 2-methyl-1,4-cyclohexanediol.

[0097]

[0098] Regarding tricyclodecanediol and pentacyclopentadecanediol as the alicyclic dihydroxy compound represented by the general formula (III), R 2 Various isomers are represented by the following general formula (IIIb) (wherein n represents 0 or 1).

[0099]

[0100] Regarding decahydronaphthalene diol or tricyclotetradecane diol as the alicyclic dihydroxy compound represented by the general formula (III), R 2 Various isomers represented by the following general formula (IIIc) (wherein m represents 0 or 1). Specific examples of such isomers include 2,6-decalin, 1,5-decalin, and 2,3-decalin.

[0101]

[0102] The norbornanediol as the alicyclic dihydroxy compound represented by the general formula (III) includes R 2 Various isomers represented by the following general formula (IIId) As such isomers, specifically, 2,3-norbornanediol, 2,5-norbornanediol, etc. can be used.

[0103]

[0104] The alicyclic dihydroxy compound represented by the general formula (III) is adamantanediol, which includes R 2 Various isomers are represented by the following general formula (IIIe). As such isomers, specifically, 1,3-adamantanediol and the like can be used.

[0105]

[0106] Among the specific examples of the alicyclic dihydroxy compounds, cyclohexanedimethanols, tricyclodecanedimethanols, adamantanediols, and pentacyclopentadecanedimethanols are particularly preferred. From the viewpoint of easy availability and ease of handling, 1,4-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,2-cyclohexanedimethanol, and tricyclodecanedimethanol are preferred. In the present invention, tricyclodecanedimethanol is preferably used as the dihydroxy compound (B).

[0107] Examples of the aliphatic dihydroxy compounds that can be used in the present invention include ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, 1,4-butylene glycol, 1,3-butylene glycol, 1,2-butylene glycol, 1,5-heptanediol, and 1,6-hexanediol. Examples of the oxyalkylene glycols that can be used in the present invention include diethylene glycol, triethylene glycol, tetraethylene glycol, and polyethylene glycol.

[0108] Examples of the aromatic dihydroxy compound that can be used in the present invention include 2,2-bis(4-hydroxyphenyl)propane [= bisphenol A], 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3,5-diethylphenyl)propane, 2,2-bis(4-hydroxy-(3,5-diphenyl)phenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, 2,2-bis(4-hydroxyphenyl)pentane, 2,4′-dihydroxy-diphenylmethane, bis(4-hydroxyphenyl)methane, bis(4-hydroxy-5-nitrophenyl)methane, 1,1-bis(4-hydroxyphenyl)pentane, and 1,1-bis(4-hydroxyphenyl)pentane. phenyl)ethane, 3,3-bis(4-hydroxyphenyl)pentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)sulfone, 2,4'-dihydroxydiphenylsulfone, bis(4-hydroxyphenyl)sulfide, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dichlorodiphenyl ether, 4,4'-dihydroxy-2,5-diethoxydiphenyl ether, 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene, 9,9-bis[4-(2-hydroxyethoxy-2-methyl)phenyl]fluorene, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-2-methylphenyl)fluorene.

[0109] As diols having a cyclic ether structure that can be used in the present invention, for example, spirodiols and dioxanediols can be cited. It should be noted that the above-mentioned exemplified compounds are examples of alicyclic dihydroxy compounds, aliphatic dihydroxy compounds, oxyalkylene glycols, aromatic dihydroxy compounds, and diols having a cyclic ether structure that can be used in the present invention, but are not limited thereto. One or more of these compounds can be used together with the dihydroxy compound represented by formula (4).

[0110] By using these dihydroxy compounds (B), it is possible to obtain effects such as improved flexibility, improved heat resistance, and improved moldability that are consistent with the purpose. The ratio of the dihydroxy compound (A), such as the dihydroxy compound represented by formula (4), to the total dihydroxy compounds constituting the polycarbonate resin of the present invention is not particularly limited, and is preferably 10 mol% or more, more preferably 40 mol% or more, and further preferably 60 mol% or more, and is preferably 90 mol% or less, more preferably 80 mol% or less, and further preferably 70 mol% or less. If the content ratio of the structural unit derived from other dihydroxy compounds is too much, the performance such as optical properties may be reduced.

[0111] When an alicyclic dihydroxy compound is used among the above-mentioned other dihydroxy compounds, the ratio of the total of the dihydroxy compound (A), for example, the dihydroxy compound represented by formula (4) and the alicyclic dihydroxy compound to the total dihydroxy compounds constituting the polycarbonate is not particularly limited, but is preferably 80 mol% or more, more preferably 90 mol% or more, and even more preferably 95 mol% or more.

[0112] In addition, the content ratio of the structural unit derived from the dihydroxy compound (A), for example, the dihydroxy compound represented by formula (4), and the structural unit derived from the alicyclic dihydroxy compound in the polycarbonate resin of the present invention can be selected at any ratio, preferably the structural unit derived from the dihydroxy compound represented by formula (4): the structural unit derived from the alicyclic dihydroxy compound = 1:99 to 99:1 (mol %), and particularly preferably the structural unit derived from the dihydroxy compound represented by formula (4): the structural unit derived from the alicyclic dihydroxy compound = 10:90 to 90:10 (mol %). If the structural unit derived from the dihydroxy compound represented by formula (4) is more and the structural unit derived from the alicyclic dihydroxy compound is less than the above range, there is a tendency to be easy to color, and conversely, if the structural unit derived from the dihydroxy compound represented by formula (4) is less and the structural unit derived from the alicyclic dihydroxy compound is more, there is a tendency that the molecular weight is difficult to increase.

[0113] Furthermore, when aliphatic dihydroxy compounds, oxyalkylene glycols, aromatic dihydroxy compounds, and diols having a cyclic ether structure are used, the ratio of the dihydroxy compound (A), for example, the dihydroxy compound represented by formula (4), and the sum of these various dihydroxy compounds to the total dihydroxy compounds constituting the polycarbonate is not particularly limited and can be selected at any ratio. In addition, the ratio of the structural unit derived from the dihydroxy compound (A), for example, the dihydroxy compound represented by formula (4), and the structural unit derived from these various dihydroxy compounds is not particularly limited and can be selected at any ratio.

[0114] The details of the polycarbonate-based resin are described in, for example, Japanese Patent Application Laid-Open No. 2012-31370, the contents of which are incorporated herein by reference.

[0115] D. Method for manufacturing phase difference film

[0116] The method for producing a retardation film according to an embodiment of the present invention includes stretching a resin film. The resin film is a film made of the polycarbonate resin described in the above section C.

[0117] In one embodiment, the phase difference film can be made by biaxial stretching. Biaxial stretching can be simultaneous biaxial stretching or sequential biaxial stretching. The stretching ratio in the length direction is preferably more than 1.0 times and less than 2.0 times, more preferably 1.1 times to 1.5 times. The stretching ratio in the width direction is preferably 1.6 times to 2.2 times, more preferably 1.8 times to 2.0 times. By stretching the film formed by the above-mentioned polycarbonate resin at this stretching ratio, not only the desired optical properties can be achieved, but also very excellent mechanical properties (such as irregular shape processability and dimensional stability) can be achieved.

[0118] The stretching temperature of the resin film is preferably Tg-30°C to Tg+30°C, more preferably Tg-10°C to Tg+25°C, and further preferably Tg+8°C to Tg+20°C. By stretching at such a temperature, a retardation film having appropriate characteristics can be obtained in the present invention. It should be noted that Tg is the glass transition temperature of the constituent material of the film.

[0119] By using a phase difference film formed by stretching a resin film containing a polycarbonate resin as described above by selecting the stretching method and stretching conditions as described above, it is possible to obtain a polarizing plate with a phase difference layer in which whitening and cracking in a sebum resistance test are suppressed and irregular shape processability and dimensional stability are excellent.

[0120] Example

[0121] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. It should be noted that the measuring method and evaluation method of each characteristic are as follows.

[0122] (1) In-plane phase difference and wavelength dispersion characteristics

[0123] The phase difference films obtained in the examples and comparative examples were cut into pieces of 4 cm in length and 4 cm in width to serve as measurement samples. The in-plane phase difference Re(550) was measured for the measurement samples using the product name "Axoscan" manufactured by Axometrics. Furthermore, Re(450) was also measured, and Re(450) / Re(550) was calculated.

[0124] (2) Moisture permeability

[0125] The retardation films obtained in the examples and comparative examples were tested for their water vapor permeability in an atmosphere of 40°C and 92%RH over an area of ​​1m2 in 24 hours according to the water vapor permeability test (cup method) of JIS Z 0208. 2 The amount of water vapor in the sample (g).

[0126] (3) Phase difference change

[0127] The phase difference film obtained in the examples and comparative examples was cut into 5 cm × 5 cm pieces, and an adhesive was applied to one side of the film using a hand roller, and the adhesive surface was applied to one side of an alkali glass to obtain a test piece. The test piece was stored in an oven at a temperature of 65°C and a humidity of 90% for 500 hours (humidification test), and the phase difference change (%) before and after the test was calculated.

[0128] (4) Irregular shape processing test

[0129] The polarizing plates with phase difference layers obtained in the examples and comparative examples were irradiated with CO2 laser at 3Kw energy, and cut along the flow direction of the film and in the direction perpendicular to the flow direction to obtain a 200mm×200mm measurement sample. The cut portion was observed using a laser microscope, and if no cracks were generated, it was recorded as 0, and if cracks were generated and / or it could not be cut, it was recorded as ×.

[0130] (5) Sebum resistance test

[0131] The polarizing plates with phase difference layers obtained in the examples and comparative examples were cut into 5 cm × 5 cm, adhesive was applied to one side with a hand roller, and the adhesive surface was applied to one side of an alkali glass to obtain a test piece. The obtained test piece was immersed in an oleic acid solution at 65°C and 90% RH for 72 hours, and when it was transparent after removal, it was recorded as 0, and when it was whitened or cracked, it was recorded as ×.

[0132] (6) Dimensional shrinkage

[0133] The polarizing plate with a phase difference layer obtained in the embodiment and the comparative example is cut into a width of 100mm and a length of 100mm (test piece), and scratches are made in a cross shape at the four corners. The length (mm) before heating in the length direction (MD direction) and the width direction (TD direction) of the central part of the cross scratch is measured by a CNC three-dimensional measuring machine (MITUTOYO, LEGEX774). After that, it is put into an oven and heat-treated (temperature 65°C, humidity 90%). After cooling naturally at room temperature for 1 hour, the length (mm) after heating in the MD direction and TD direction of the four points of the four corners is measured again by a CNC three-dimensional measuring machine, and its measured value is substituted into the following formula to obtain the heat shrinkage rate of each direction of the MD direction and the TD direction.

[0134] Thermal shrinkage (%) = [[length before heating (mm) - length after heating (mm)] / length before heating (mm)] × 100

[0135] When the heat shrinkage rate was 0% to 0.5%, it was recorded as 0, and when the shrinkage rate was 0.5% or more, it was recorded as ×.

[0136] [Example 1]

[0137] 1. Preparation of resin film

[0138] In the reaction vessel, relative to 81.98 parts by mass of isosorbide (hereinafter sometimes abbreviated as "ISB"), 47.19 parts by mass of tricyclodecane dimethanol (hereinafter sometimes abbreviated as "TCDDM"), 175.1 parts by mass of diphenyl carbonate (hereinafter sometimes abbreviated as "DPC") and 0.979 parts by mass of a 0.2% aqueous solution of cesium carbonate as a catalyst are put in, and under a nitrogen atmosphere, as a process of the first stage of the reaction, the heating tank temperature is heated to 150°C, and the raw materials are dissolved while stirring as needed (about 15 minutes). Then, the pressure is set to 13.3kPa from normal pressure, and the heating tank temperature is raised to 190°C while consuming 1 hour, and the phenol produced is taken out of the reaction vessel. After the reaction vessel as a whole is kept at 190°C for 15 minutes, as a process of the second stage, the pressure in the reaction vessel is set to 6.67kPa, and the heating tank temperature is raised to 230°C while consuming 15 minutes, and the phenol produced is taken out of the reaction vessel. Since the stirring torque of the stirrer gradually increased, it took 8 minutes to raise the temperature to 250°C, and further, the pressure in the reaction container was made to be less than 0.200 kPa in order to remove the generated phenol. After reaching the specified stirring torque, the reaction was terminated, and the generated reactant was extruded into water to obtain pellets of polycarbonate resin. The obtained polycarbonate resin was vacuum dried at 80°C for 5 hours, and then a polycarbonate resin film with a thickness of 60 μm was prepared using a film forming device equipped with a single screw extruder (manufactured by Toshiba Machine Co., Ltd., barrel setting temperature: 250°C), a T die (width: 300 mm, setting temperature: 250°C), a cooling roller (setting temperature: 120-130°C) and a winder.

[0139] 2. Preparation of phase difference film

[0140] Using a simultaneous biaxial stretching machine, the unstretched polycarbonate resin film is subjected to preheating and simultaneous biaxial stretching to obtain a phase difference film. The preheating temperature is set to 137°C. The stretching temperature is set to 137°C (Tg+10°C), the stretching ratio in the length direction is set to 1.2 times, and the stretching ratio in the width direction is set to 1.9 times. The in-plane phase difference Re(550) of the obtained phase difference film is 135nm, Re(450) / Re(550) is 1.02, and the moisture permeability is 88g / m 2 ·24h, the phase difference changes to 0.6%.

[0141] 3. Production of polarizing plate

[0142] As the resin substrate, a long amorphous polyethylene terephthalate copolymer film (thickness: 100 μm) having a Tg of about 75° C. was used, and one surface of the resin substrate was subjected to a corona treatment.

[0143] 13 parts by weight of potassium iodide was added to 100 parts by weight of a PVA-based resin obtained by mixing polyvinyl alcohol (polymerization degree of 4200, saponification degree of 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER") in a ratio of 9:1, and the resulting product was dissolved in water to prepare a PVA aqueous solution (coating liquid).

[0144] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a 13 μm-thick PVA-based resin layer to produce a laminate.

[0145] The obtained laminate was uniaxially stretched to 2.4 times in the longitudinal direction (length direction) in an oven at 130° C. (in-air auxiliary stretching treatment).

[0146] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).

[0147] Next, the film was immersed in a dyeing bath (an iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 relative to 100 parts by weight of water) at a liquid temperature of 30° C. for 60 seconds while adjusting the concentration so that the single body transmittance (Ts) of the finally obtained polarizer reaches the desired value (dyeing treatment).

[0148] Next, the film was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).

[0149] Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration of 4 wt %, potassium iodide concentration of 5 wt %) at a liquid temperature of 70°C, and uniaxially stretched (underwater stretching treatment) in the longitudinal direction (length direction) between rollers with different circumferential speeds in such a manner that the total stretching ratio reached 5.5 times.

[0150] Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).

[0151] Thereafter, the film was dried in an oven maintained at about 90° C. while being brought into contact with a SUS heating roll maintained at a surface temperature of about 75° C. (drying shrinkage treatment).

[0152] In this manner, a polarizer having a thickness of about 5 μm was formed on the resin substrate, thereby obtaining a polarizing plate having a structure of resin substrate / polarizer.

[0153] Furthermore, on the surface of the obtained polarizer on the opposite side of the resin substrate, a cycloolefin film (manufactured by Japan ZEON Corporation, trade name "ZEONOR") is pasted as a protective layer with the help of an ultraviolet curing adhesive. Specifically, the curing adhesive is applied in a manner that the total thickness reaches about 1.0 μm, and a roller machine is used for bonding. Thereafter, UV light is irradiated from the cycloolefin film side to cure the adhesive. Next, the resin substrate is peeled off to obtain a polarizing plate having a structure of cycloolefin film (protective layer) / polarizer. The in-plane phase difference of the protective layer is 135 nm. The angle between the slow axis of the protective layer and the absorption axis of the polarizer is substantially parallel.

[0154] 4. Preparation of polarizing plate with phase difference layer

[0155] The phase difference layer film is attached to the polarizer side of the polarizing plate. The angle between the absorption axis of the polarizer and the slow axis of the phase difference film is set to 45°. Furthermore, a hard coating layer is formed on the side of the phase difference film opposite to the polarizer to obtain a polarizing plate with a phase difference layer. The obtained polarizing plate with a phase difference layer is provided for the evaluation of (4) to (6) above. The results are shown in Table 1.

[0156] [Example 2]

[0157] The same operation as in Example 1 was performed except that the stretching temperature of the resin film was set to Tg+15°C to obtain a retardation film. The in-plane retardation Re (550) of the obtained retardation film was 137 nm, and the water vapor permeability was 88 g / m 2 ·24h, the phase difference change is 0.6%. The same operation as in Example 1 was performed except that the phase difference film was used and a general polycarbonate resin film was used as the protective layer to obtain a polarizing plate with a phase difference layer. The in-plane phase difference of the protective layer was 135nm. The obtained polarizing plate with a phase difference layer was subjected to the evaluations of (4) to (6) above. The results are shown in Table 1.

[0158] [Example 3]

[0159] The same operation as in Example 1 was performed except that the stretching temperature of the resin film was set to Tg+20°C to obtain a retardation film. The in-plane retardation Re (550) of the obtained retardation film was 134 nm, and the water vapor permeability was 86 g / m 2 ·24h, the phase difference changed to 0.6%. The same operation as in Example 1 was performed except that the phase difference film was used and an acrylic resin film (manufactured by Mitsubishi Rayon Co., Ltd., trade name: ACRYPET VH, Tg: 113°C) was used as the protective layer to obtain a polarizing plate with a phase difference layer. The in-plane phase difference of the protective layer was 0.3nm. The obtained polarizing plate with a phase difference layer was subjected to the evaluations of (4) to (6) above. The results are shown in Table 1.

[0160] [Comparative Example 1]

[0161] The resin film used was a cycloolefin resin film (manufactured by ZEON Corporation of Japan, trade name "ZEONOR"), and the stretching temperature was set to Tg + 20 ° C. The same operation as in Example 1 was performed to obtain a retardation film. The in-plane retardation Re (550) of the obtained retardation film was 135 nm, Re (450) / Re (550) was 1.01, and the moisture permeability was 18 g / m 2 After 24 hours, the phase difference changed to 0.2%. Using this phase difference layer, the same operation as in Example 1 was performed to obtain a polarizing plate with a phase difference layer. The obtained polarizing plate with a phase difference layer was subjected to the above-mentioned evaluations (4) to (6). The results are shown in Table 1.

[0162] [Comparative Example 2]

[0163] The resin film used was a cycloolefin resin film (manufactured by ZEON Corporation of Japan, trade name "ZEONOR"), and the stretching temperature was set to Tg + 20 ° C. The same operation as in Example 1 was performed to obtain a retardation film. The in-plane retardation Re (550) of the obtained retardation film was 135 nm, Re (450) / Re (550) was 1.01, and the moisture permeability was 18 g / m 2 ·24h, the phase difference change is 0.2%. The same operation as in Example 1 was performed except that the phase difference film was used and a general polycarbonate resin film was used as the protective layer to obtain a polarizing plate with a phase difference layer. The in-plane phase difference of the protective layer was 135nm. The obtained polarizing plate with a phase difference layer was subjected to the evaluations of (4) to (6) above. The results are shown in Table 1.

[0164] [Comparative Example 3]

[0165] The resin film used was a cycloolefin resin film (manufactured by ZEON Corporation of Japan, trade name "ZEONOR"), and the stretching temperature was set to Tg + 20 ° C. The same operation as in Example 1 was performed to obtain a retardation film. The in-plane retardation Re (550) of the obtained retardation film was 136 nm, Re (450) / Re (550) was 1.01, and the moisture permeability was 20 g / m 2 ·24h, the phase difference change is 0.2%. The same operation as in Example 1 was performed except that the phase difference film was used and the protective layer was an acrylic resin film (manufactured by Mitsubishi Rayon Co., Ltd., trade name: ACRYPET VH, Tg: 113°C), to obtain a polarizing plate with a phase difference layer. The in-plane phase difference of the protective layer was 0.3nm. The obtained polarizing plate with a phase difference layer was subjected to the evaluations of (4) to (6) above. The results are shown in Table 1.

[0166] [Comparative Example 4]

[0167] The rotating axis of the brushing roller is adjusted to 45° counterclockwise relative to the length direction of the triacetyl cellulose (TAC) film (manufactured by Fujifilm Corporation) and brushed. The TAC film that has been brushed is coated with liquid crystal to obtain a liquid crystal coated triacetyl cellulose (TAC) film. The resin film uses the above liquid crystal coated TAC and is not stretched. Except for this, the same operation as in Example 1 is performed to obtain a phase difference film. The in-plane phase difference Re(550) of the obtained phase difference film is 0.1nm, Re(450) / Re(550) is 1.09, and the moisture permeability is 320g / m 2 After 24 hours, the phase difference changed by 2.1%. Using this phase difference layer, the same operation as in Example 1 was performed to obtain a polarizing plate with a phase difference layer. The obtained polarizing plate with a phase difference layer was subjected to the above-mentioned evaluations (4) to (6). The results are shown in Table 1.

[0168] [Comparative Example 5]

[0169] The same operation as in Example 1 was performed except that the resin film used the above-mentioned liquid crystal coated TAC and was not stretched to obtain a retardation film. The in-plane retardation Re(550) of the obtained retardation film was 0.1 nm, Re(450) / Re(550) was 1.09, and the moisture permeability was 337 g / m 2 ·24h, the phase difference changed to 1.8%. The same operation as in Example 1 was performed except that the phase difference film was used and an acrylic resin film (manufactured by Mitsubishi Rayon Co., Ltd., trade name: ACRYPET VH, Tg: 113°C) was used as the protective layer to obtain a polarizing plate with a phase difference layer. The in-plane phase difference of the protective layer was 0.6nm. The obtained polarizing plate with a phase difference layer was subjected to the evaluations of (4) to (6) above. The results are shown in Table 1.

[0170] [Comparative Example 6]

[0171] The same operation as in Example 1 was performed except that the stretching temperature of the resin film was set to Tg+7°C to obtain a retardation film. The in-plane retardation Re (550) of the obtained retardation film was 200 nm, and the water vapor permeability was 88 g / m 2 After 24 hours, the phase difference changed to 0.8%. Using this phase difference layer, the same operation as in Example 1 was performed to obtain a polarizing plate with a phase difference layer. The obtained polarizing plate with a phase difference layer was subjected to the evaluations of (4) to (6). The results are shown in Table 1.

[0172] [Table 1]

[0173]

[0174] It is clear from Table 1 that the phase difference film of the embodiment of the present invention is excellent in moisture permeability, phase difference change, irregular shape processability test, sebum resistance test and dimensional stability test. It can be inferred that this is achieved by the following operation: the polarizing plate with a phase difference layer has a phase difference layer and a polarizing plate in sequence, the polarizing plate has a polarizer and a protective layer, the phase difference layer contains a specific polycarbonate resin, and the polarizing plate with a phase difference layer is obtained by stretching by a specific stretching method and stretching conditions.

[0175] Industrial Applicability

[0176] The polarizing plate with a retardation layer according to the embodiment of the present invention can be suitably used in an image display device.

[0177] Description of Reference Numerals

[0178] 10 polarizing plates

[0179] 11 polarizer

[0180] 12 First protective layer

[0181] 13 Second protective layer

[0182] 20 Phase difference layer

[0183] 100 Polarizing plate with phase difference layer

Claims

1. A polarizing plate with a phase difference layer, which is arranged on the viewing side of an image display device, The polarizing plate with a phase difference layer comprises a phase difference layer and a polarizing plate in order from the viewing side, and the polarizing plate comprises a polarizer and a protective layer. The phase difference layer contains a polycarbonate resin. The polycarbonate resin is composed only of a structural unit derived from a dihydroxy compound represented by the following formula (4), a structural unit derived from an alicyclic dihydroxy compound represented by the following general formula (II), and a carbonate group derived from a carbonic acid diester, wherein R 1 The structure shown in (IIb) below, n=0, The Re(450) / Re(550) of the phase difference layer is 0.98 to 1.03, and the Re(550) of the phase difference layer is 80 nm to 190 nm. HOCH2-R 1 -CH2OH(II) 2. The polarizing plate with a phase difference layer according to claim 1, wherein no cracks are generated in the cut portion in the following irregular shape processability test, Irregular shape processability test: The polarizing plate with the phase difference layer was irradiated with CO2 laser at an energy of 3 Kw, and the polarizing plate with the phase difference layer was cut along the flow direction and the direction perpendicular to the flow direction.

3. The polarizing plate with a phase difference layer according to claim 1 or 2, which does not produce whitening and cracks in the following sebum resistance test, Sebum resistance test: After the pressure-sensitive adhesive layer of the polarizing plate with a retardation layer was attached to one surface of an alkali glass, the plate was immersed in an oleic acid solution under the conditions of 65° C. and 90% RH for 72 hours.

4. The polarizing plate with a retardation layer according to claim 1 or 2, wherein the thermal shrinkage calculated in the following dimensional stability test is 0% to 0.5%, Dimensional stability test: The lengths of the polarizing plate with a phase difference layer before heating in the longitudinal direction and the width direction are measured, and then the polarizing plate with a phase difference layer is heated at a temperature of 65° C. and a humidity of 90%. After naturally cooling at room temperature for 1 hour, the lengths of the polarizing plate with a phase difference layer after heating in the longitudinal direction and the width direction are measured, and the measured values ​​are substituted into the following formula to calculate the heat shrinkage rate. Thermal shrinkage (%) = [[length before heating - length after heating] / length before heating] × 100 in, The unit of the length before heating is mm, and the unit of the length after heating is mm.

5. The polarizing plate with a phase difference layer according to claim 1 or 2, wherein: The moisture permeability of the phase difference layer is 100 g / m 2 Less than 24 hours. 6 . The polarizing plate with a retardation layer according to claim 1 , wherein a change in retardation of the retardation layer after storage for 500 hours under conditions of a temperature of 65° C. and a humidity of 90% is 1.5% or less. 7 . The polarizing plate with a retardation layer according to claim 1 , which is in a long strip shape, and the retardation layer is an obliquely stretched film having a slow axis in a direction forming an angle of 40° to 50° with respect to the longitudinal direction.